Changes in the economics of coffee production between 2008 and 2019: a tale of two Central American countries - Leiva, Benjamín; Vargas, Adrián; Casanoves, Fernando; Haggar, Jeremy (Frontiers in Sustainable Food Systems, 2024)
Increasing costs of coffee production relative to coffee prices has led to concern across the industry of lack of profitability of coffee production especially for smallholders who comprise a large majority of producers. This study compares coffee production costs and income over a decadal interval of 2008 versus 2019 for coffee farmers in some of the main coffee growing regions of Costa Rica and Guatemala. Costs and income were collected by farmer recall using a standard questionnaire with trained research surveyors. Net income as assessed by EBITDA (earnings before interest, taxes, depreciation and amortization) increased by about 30% in Costa Rica, but declined to a third of its 2008 level in Guatemala. Agronomic costs of production per hectare increased by 31% in Costa Rica and 62% in Guatemala, mostly due to increased labor costs (higher daily wage rates), while fertilizer usage increased but unit costs remained stable. Gross income was stable in Guatemala but increased in Costa Rica due to receiving significantly higher prices for their coffee in 2019 compared to 2008, while in Guatemala prices declined. Nevertheless, the response was not uniform between farms in Costa Rica while high and medium productivity groupings of farms had higher EBITDA, low and very low productivity farms experienced a decline similar to Guatemala. The difference in performance of farm groups in Costa Rica was due to a decline in production per hectare of the lower productivity group; while the difference between Guatemala and Costa Rica was firstly due to price differences, and secondarily due to lower productivity of some farm groups. The investment of Costa Rican farmers was undoubtedly supported by the substantially increased price received by farmers (as compared to Guatemala), reflected in the increase in export price of coffee from Costa Rica relative to Guatemala. This shows the importance of farmers receiving higher prices for their produce in enabling them to cover increasing production costs, invest in increasing productivity and maintain profitability.